Transcriptional engineering for value enhancement of oilseed crops: a forward perspective - Kaushal, Charli; Sachdev, Mahak; Parekh, Mansi; Gowrishankar, Harini; Jain, Mukesh; Sankaranarayanan, Subramanian; Pathak, Bhuvan (Frontiers in Genome Editing, 2025)
Plant-derived oils provide 20%–35% of dietary calories and are a primary source of essential omega-6 (linoleic) and omega-3 (α-linolenic) fatty acids. While traditional breeding has significantly increased yields in key oilseed crops like soybean, sunflower, canola, peanut, and cottonseed, overall gains have plateaued over the past few decades. Oilseed crops also experience substantial yield losses in both prime and marginal agricultural areas due to biotic and abiotic stresses and shifting agro-climates. Recent genomic, transcriptomic, and metabolomics research has expanded our understanding of the genetic and physiological control of fatty acid biosynthesis and composition. Many oilseed species have inherent stress-combating mechanisms, including transcription factor regulation. Advances in genome editing tools like CRISPR/Cas9 offer precise genetic modifications, targeting transcription factors and binding sites to enhance desirable traits, such as the nutritional profile and chemical composition of fatty acids. This review explores the application of genome editing in oilseed improvement, covering recent progress, challenges, and future potential to boost yield and oil content. These advancements could play a transformative role in developing resilient, nutritious crop varieties essential for sustainable food security in a changing climate.